2021
DOI: 10.1002/ca.23760
|View full text |Cite
|
Sign up to set email alerts
|

The state of anatomical donation programs amidst the SARS‐CoV‐2 (Covid‐19) pandemic

Abstract: The inclusion of human body dissection in anatomical science curricula has been described as a critical educational experience for the mastery of anatomical structures and concepts. To ensure that body donors are ethically acquired and suitable for anatomy education, Anatomical Donation Programs (ADPs) are tasked with the responsibility of acquiring body donors for basic and clinical science curricula. Considering the personal and institutional impact of SARS‐CoV‐2, a national survey was conducted to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Due to the limited access to anatomical specimens of adults, there was a strong need to look for alternative sources of biological material (Ghosh 2017;McCumber et al 2021). Fetal collections assembled in many anatomical laboratories in the 19th and 20th centuries could be such a source (Rohan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited access to anatomical specimens of adults, there was a strong need to look for alternative sources of biological material (Ghosh 2017;McCumber et al 2021). Fetal collections assembled in many anatomical laboratories in the 19th and 20th centuries could be such a source (Rohan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy education has been deeply impacted by the pandemic. Most Anatomical Donation Programs worldwide faced a critical shortage of body donors, and profound changes in the traditional way of teaching (Ravi, 2020; Singal et al, 2020; Manzanares‐Céspedes et al, 2021; McCumber et al, 2021). This led to new challenges since a direct approach to “hands‐on” anatomy education has always been perceived by the community to be an indispensable component for subject mastery.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find in the literature publications related to the impact of the pandemic on the willingness to donate. However, McCumber et al (2021) reported 50% of reduction in donations recieved by the United States universities and only 5.6% of the donation programs participating at the survey informed an increase. Many articles were published evaluating the pandemic circumstances and consequences, however most of them were editorials or not data based ones (Bond and Franchi, 2020;Dost et al, 2020;Franchi, 2020;Murlimanju et al, 2020;Puljak et al, 2020;Singal et al, 2020;Banovac et al, 2021;Singal et al, 2021;Manzanares Cespedes et al, 2021;Suarez-Escudero et al, 2021;Gonzalez Fernandez and Salazar Sanchez, 2022).…”
Section: Discusionmentioning
confidence: 94%